A Sensor-based Indoor Positioning Algorithm for Smart-Tour Applications - Vinh, Tran-Quang; Phung, Dinh Phuc (Old Journal, 2018)
This article presents an indoor positioning algorithm using accelerometer, gyroscope, and magnetic sensors to determine the location of travel users, to provide location-based services for users on intelligent travel guide systems. The main contributions of the proposal method on this paper are the application of a Kalman filter to eliminate interference of sensor signals that are received from integrated sensors on common smartphones, to handle the time velocity drift when user moving smartphone while standing in place, and therefore, to increase the positioning accuracy. The experiment results show that the proposed positioning algorithm achieves decimeter accuracy in indoor environment, which is suitable for positioning applications such as smart-tour applications.